Fundamentals of HIV medicine 2021 - Hardy, W. David (William David), 1955-; American Academy of HIV Medicine (New York, NY : Oxford University Press, 2021)
'Fundamentals of HIV Medicine 2021' is the AAHIVM's end-to-end clinical resource for the treatment of individuals with HIV/AIDS. Now updated with HIV workforce strains and PrEP, newly emerging antiretroviral treatment options, and the evolving effects of COVID-19 on HIV care.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 17, 2021).
Keywords: HIV infections